2016
DOI: 10.12973/eurasia.2017.00617a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect on User Perception and Performance of Static and Dynamic Contents Deployed in Augmented Reality based Learning Application

Abstract: Nowadays, the use of technology to improve teaching and learning experiences in the classroom has been promoted. One of these technologies is augmented reality, which allows overlaying layers of virtual information on real scene with the aim of increasing the perception that user has of reality. Augmented reality has proved to offer several advantages in the educational context, i.e. increasing learning engagement and increasing understanding of some topics, especially when spatial skills are involved. Content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Their results showed that using AR technology in course provided students to increase their academic performance, motivation, and satisfaction. Montoya et al [66] developed an AR mobile application and they compared effect of static and dynamic content on students' science learning. Their results revealed that using dynamic content in AR applications helped students to enhance learning perception and performance.…”
Section: Using Augmented Reality In Graduate Educationmentioning
confidence: 99%
“…Their results showed that using AR technology in course provided students to increase their academic performance, motivation, and satisfaction. Montoya et al [66] developed an AR mobile application and they compared effect of static and dynamic content on students' science learning. Their results revealed that using dynamic content in AR applications helped students to enhance learning perception and performance.…”
Section: Using Augmented Reality In Graduate Educationmentioning
confidence: 99%
“…R is a 3 × 3 rotation matrix and t is 3 × 1. The mapping matrix of transformation matrix T from real space to unity3d space is as follows: (7) In this way, a one-to-one correspondence relationship is established between the real space and the coordinates of the marker points in the virtual space. Each virtual body PX in the virtual space can be uniquely mapped to the corresponding position entity PS on the human organs in the real space, which is converted into: In the left-handed system, the matrix RX corresponding to the rotation angle P ° about the x-axis…”
Section: High Precision Automatic Registration Of Augmented Realitymentioning
confidence: 99%
“…According to the observer's current field of view, the coordinate system is reestablished and the virtual object is displayed in the following ways. This process to the correct position is called tracking [7][8].…”
Section: Key Technologies Of Augmented Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…The design experiment followed some of the methods of the experiment done in Montoya, et al [13]. After gathering data from the experiment, data analysis methods were carried out by the participants.…”
Section: Experimental Design and Data Analysismentioning
confidence: 99%